PERAN BUDAYA SEKOLAH DALAM MEMBENTUK KARAKTER RELIGIUS SISWA KELAS III DI SD IT ROBBANI BANJARBARU - Astuti Kusuma Dewi; Wulida Makhtuna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Strengthening religious character at the elementary school level is an essential component of developing students’ personalities based on moral and religious values. One effort that schools can undertake is developing a school culture manifested through habituation, role modelling, and continuously implemented religious activities. This study aims to analyse the implementation of school culture and its contribution to developing the religious character of third-grade students at SD IT Robbani Banjarbaru. This study employed a descriptive qualitative approach involving the principal, third-grade teachers, and students as research participants. Data were collected through observation, semi-structured interviews, and documentation. The data were subsequently analysed through data reduction, data presentation, and conclusion drawing, while source and technique triangulation were applied to ensure data credibility. The findings indicate that a religious school culture was developed through greeting and shaking hands with teachers, performing congregational prayers, and regularly reciting the Qur’an. These practices functioned not merely as school routines but also as a means of internalising religious values through habituation and teacher role modelling. Students’ religious character was reflected in their respect for teachers, courteous behaviour, discipline in performing religious practices, and growing appreciation of the Qur’an. Therefore, school culture plays a strategic role in developing students’ religious character through a consistent, supportive, and religiously grounded educational environment.